Lack of miR-379/miR-544 Cluster Resists High-Fat Diet-Induced Obesity and Prevents Hepatic Triglyceride Accumulation in Mice - Cao, Congcong; Duan, Peng; Li, Wencun; Guo, Yang; Zhang, Jin; Gui, Yaoting; Yuan, Shuiqiao (Frontiers in Cell and Developmental Biology, 2021)
Nonalcoholic fatty liver disease (NAFLD) affects obesity-associated metabolic syndrome, which exhibits hepatic steatosis, insulin insensitivity and glucose intolerance. Emerging evidence suggests that microRNAs (miRNAs) are essential for metabolic homeostasis of liver tissues. Many hepatic miRNAs located in the miR-379/miR-544 cluster were significantly increased in leptin-receptor-deficient type 2 mice (db/db), a mouse model of diabetes. However, the function of miR-379/miR-544 cluster in the process of hepatic steatosis remains unclear. Here, we report that the novel function of miR-379/miR-544 cluster in regulating obesity-mediated metabolic dysfunction. Genetical mutation of miR-379/miR-544 cluster in mice displayed resistance to high-fat diet (HFD)-induced obesity with moderate hepatic steatosis and hypertriglyceridemia. In vitro studies revealed that silencing of miR-379 in human hepatocellular carcinoma (HepG2) cells ameliorated palmitic acid-induced elevation of cellular triglycerides, and overexpression of miR-379 had the opposite effect. Moreover, Igf1r (Insulin-like growth factor 1 receptor) and Dlk1 (Delta-like homolog 1) were directly targeted by miR-379 and miR-329, respectively, and elevated in the livers of the miR-379/miR-544 cluster knockout mice fed on HFD. Further transcriptome analyses revealed that the hepatic gene expressions are dysregulated in miR-379/miR-544 knockout mice fed with HFD. Collectively, our findings identify the miR-379/miR-544 cluster as integral components of a regulatory circuit that functions under conditions of metabolic stress to control hepatic steatosis. Thus, this miRNA cluster provides potential targets for pharmacologic intervention in obesity and NAFLD.